DOID: A Lexical Analyzer for Understanding Mid-Level Compilation Processes (International Journal of Engineering and Computer Science, 2016)
This research was undertaken to give students in the local Nigerian environment a hands-on, practical and direct knowledge of Compiler Construction and Automata Theory, with the motivation to make it the Country’s first programming language. The project was carried out using the Lex/Flex Lexical Analyzer Generator and the C Language. Compiler construction and automata theory has been one of the tougher subjects for local students in the Nigerian region. The purpose of this research is to make our programmers better understand the processes in program compilation and also catch up with the interest of nonprogrammers who may become fascinated by the exquisiteness of programming when it is only at the highest level, which is more like speaking to a fellow human. Locals and students will also be more interested in the subject matter when they are to learn a Language developed in their country.